2021
DOI: 10.1080/13669877.2021.1957987
|View full text |Cite
|
Sign up to set email alerts
|

Trust, mistrust and distrust as blind spots of Social Licence to Operate: illustration via three forerunner countries in nuclear waste management

Abstract: b Groupe de sociologie pragmatique et réflexive (GsPr), ecole des hautes etudes en sciences sociales, Paris, france; c science Policy research unit (sPru), university of sussex, Brighton, uk; d faculty of Management and Business,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Trust and social justice can be strengthened by improving public communication, increasing information transparency by resident's on-site visit to WIPs, conducting quality monitoring, and compensation policy (Lu 2023). In addition, social license to operate to enhance the trust on WIP has been widely reviewed recently and reported that it was still questionable and suggested further studies (Lehtonen et al 2022). A study conducted among the residents in four cities in China living within 3 km from WIPs found that social license to operate was applicable for WIP management, but the enhancing social trust was still controversial (He et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Trust and social justice can be strengthened by improving public communication, increasing information transparency by resident's on-site visit to WIPs, conducting quality monitoring, and compensation policy (Lu 2023). In addition, social license to operate to enhance the trust on WIP has been widely reviewed recently and reported that it was still questionable and suggested further studies (Lehtonen et al 2022). A study conducted among the residents in four cities in China living within 3 km from WIPs found that social license to operate was applicable for WIP management, but the enhancing social trust was still controversial (He et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation was that participants’ attachment to place, affinity or identity with the affected area was not assessed, which would have allowed us to analyze differentiation in beliefs about risks and benefits, as well as emotional balance and acceptance level. Nor did we evaluate trust or mistrust of the project development and institutions, another variable that has been found to be relevant in other studies on mine construction ( Lehtonen et al, 2022 ). On the other hand, the data were collected at a single point in time without considering the evolution of the conflict in the area.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of SLO has come to apply to diverse sectors such as the energy and nuclear waste management (Lehtonen et al, 2022), animal-based entertainment industries (McManus, 2022), and forestry (Pimenta et al, 2021). Through this chapter, we propose to argue that SLO can be extended to development of LAWS until a coherent, broad-based international framework on the area of LAWS emerges.…”
Section: Can the Slo Model Be Extended To Laws Developers?mentioning
confidence: 99%